Pasang Surut Pemikiran Al-Syafi’I Telaah Pemikiran Qaul Qadim dan Qaul Jadid dengan Pendekatan Teori Siklus Ibnu Khaldun - A. Halil Thahir (LP2M Sekolah Tinggi Agama Islam (STAI) Madiun, 2021)
This article discusses the ups and downs of al-Shafi'i's thinking, which are three periods. First, the learning period, is the period when al-Shafi'i in Mecca, Medina, Yemen, Iraq first (pre-Baghdad). second, the period where al-Shafi'i resided in Iraq, qaul qadim, third, the period when al-Shafi'i lived in Egypt, qaul jadid. This library research examines and reveals the following issues: what are the factors behind the change in the law thoughts of al-Shafi'i ? And how did al-Shafi'i's thoughts change according to the perspective of Ibn Khaldun's cycle theory ?, using the law sociology approach, that is Ibn Khaldun's cycle theory as a knife of analysis. The theory conceptualizes the change in civilization from the condition of badawah as a condition of beginning and formation, hadarah as a phase of development and progress, to the condition of inqiradh, a period of decline. Changes in the law thoughts of al-Shafi'i from pre-qaul qadim, qaul qadim to qaul jadid were motivated and influenced by several things, namely: geographical factors, cultural factors and customs, scientific factors, social factors, economic factors, political factors, and difference factor in the use of theorem. Whereas the change experienced three conditions, namely the condition of badawah for the pre-qaul qadim phase, the condition of hadarah for the qaul qadim period, and the condition of inqiradh, during the qaul jadid period.